Análisis de modos normales de vibración en los modelos isotrópico y ortotrópico de la membrana timpánica - Martínez-Celorio, R. A.; Rodríguez Bravo, Humberto; Rodríguez Cruz, Rafael A.; Castro-Sánchez, R.; Martí-López, Luis; Vega-Corona, A. (Revista Mexicana de Ingenieria Biomedica, 2007)
An analysis of vibrational model by using Finite Element Method (FEM) of isotropic and orthotropic models of the eardrum is proposed. A human eardrum was digitized for reconstructing its geometry and be able to study the vibrational modes by means of a FEM program. The mechanical properties in each one of eardrum parts can be added inside the program to look like a real situation and simulate also the membrane connection to temporal bone as well as the contact between manubrium and malleus. Three models were analyzed, these are: isotropic where was considering contact or not between malleus and manubrium and the model orthotropic with mechanical properties distributed in radial and azimuthal directions. The models allow to analyze how influence of these changes on the vibrational modes. Advantages and disadvantages are discussed.